Paragraph Writing for Foreign Students by Using AI: English and Indonesian Analysis - Mulyanah, Euis Yanah; Muhyidin, Asep; Sjaifuddin, Sjaifuddin; Ishak, Ishak; Amarullah, Ahmad; Sumiyani, Sumiyani; Sulaeman, Agus (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
This research explores the impact of AI-assisted tools on paragraph writing for foreign students learning English and Indonesian. Writing proficiency is a critical component of language acquisition, and AI offers innovative solutions to enhance this process. This research has demonstrated the significant positive impact of AI-assisted tools on enhancing paragraph writing skills for foreign students learning English and Indonesian. Using a mixed-methods approach with combain boyh quantitative and qualitative research methods, the study provided both quantitative and qualitative evidence supporting the effectiveness of these tools. The instrument used was a standardized writing test designed to evaluate grammatical accuracy, syntactical complexity, and vocabulary range. For English Language Learners (ELL), there was a notable improvement in writing skills, with average test scores increasing from 65 to 80. Additionally, there was a 40% reduction in grammatical and syntactical errors and a 30% enhancement in vocabulary usage. Similarly, Indonesian Language Learners (ILL) experienced a rise in test scores from 60 to 75, a 35% reduction in errors, and a 25% improvement in vocabulary usage.These results underscore the benefits of AI tools in language education. In conclusion, AI-assisted tools have proven to be highly effective in improving paragraph writing skills for foreign students learning English and Indonesian. The combination of quantitative improvements in writing proficiency and positive qualitative feedback from students highlights the transformative potential of AI in language education. By providing personalized, real-time, and contextually appropriate feedback, AI tools can significantly enhance the learning experience and outcomes for foreign students.